Consumer Preference for Product Categories Sold Online and Offline - Sari, Nita Wanda (IHSA Institute, 2023)
The research purpose determines that consumers preferences for online and offline shopping at different shopping experience and determine products which choose consumers for online and offline shopping at different shopping experience. The research uses qualitative descriptive analysis obtained from the result of questionnaire through interviews with the respondent based on categories of some profession who have done shopping online or offline in Medan City. The finding of the research shows Mean Ratings of the people choose the shopping attributes such as Enjoy Shopping, Shop Quickly, Large Selection and Best Price by online shopping while the shopping attributes such as See-Touch Handle, Personal Service, Speedy Delivery and No-hassle Exchange by offline shopping. The products such as Airlines Tickets, Clothes, Elektronics Products, Health and Grooming, and other products (Shoes, Bags, Scarfs, Wallets, Accessories, Foods, Movie Vouchers and Underwear) consumers choose by online shopping. In the other hand, the people choose offline shop the products such as Books, CDs, Computer Software and Sporting Goods. The correlation value is 0.937 for the search stages and purchase stages, it means thathas the significant correlation value when the consumers choose the online and offline shopping with value of signification 0.01.